Determinación de toxoplasma Gondii InG, igM en mujeres embarazadas y su relación con el aborto en el período junio - noviembre del 2006 - Martínez Moreno, Verónica M. (2009)
The seropositividad of the populations for T. gondii at world level, and especially in latinoámerica, it has been analyzed by many investigators, in reference to the climate, altitude, occupation, urban or rural atmosphere, ethnicity and individual habits.